Historical retrospective of the economic analysis of law (II): from the old to the new economic analysis of law (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2019)
The influence of the economy into human behavior shows the connection of the economy, politics and law. If we add the existence of scarce resources together with the need to maximize results, we find the breeding ground of economic law analysis (AED), a movement that applies techniques and economic principles in the study of legal problems.From their postulates we can conclude that the law can not be understood from an exclusively legal perspective, and efficiency constitutes a prevailing criterion that determines the very notion of justice.After a more remote background (Locke, Smith, Bentham, Beccaria, Marx, Wagner, Weber, and Commons), they will follow the wake Walras, Pareto, or Buchanan. Its most renowned representatives come from the economy and law, among which we can highlight authors such as Becker, Coase, Calabresi and Posner, whose contribution to the AED will focus our study.
Keywords: law; economy; efficiency; equity; Economic Analysis of Law; firsts steps; Old and New AED